A Systematic and Narrative Review of Acupuncture Point Application Therapies in the Treatment of Allergic Rhinitis and Asthma during Dog Days - Wen, Cai-Yu-Zhu (Evid Based Complement Alternat Med, 2015)
Acupuncture point application therapies, including San-Fu-Tie and San-Fu-Jiu, have been widely employed to treat diseases with attacks in winter during dog days in China. The therapies combine Chinese herbal medicine and acupuncture points with the nature. However, the previous studies were reported to be unsystematic and incomplete. To develop a more comprehensive understanding of the effects of acupuncture point application therapies on allergic rhinitis and asthma, a systematic review of the literature up to 2015 was conducted. After filtering, eighteen randomized controlled trials (RCTs) involving 1,785 subjects were included. This systematic and narrative review shows that acupuncture point application therapies have been extensively applied in the treatment of allergic rhinitis and asthma with advantages of favorable treatment effect, convenient operation, receiving patients' good acceptability and compliance, and few side effects. Meanwhile, the study elaborated the operating process of San-Fu-Tie and San-Fu-Jiu in detail. The review may provide a reference for clinical application in future. However, the efficacy, safety, and mechanisms of San-Fu-Tie and San-Fu-Jiu in treating the above diseases need to be validated by more well-designed and fully powered RCTs in a larger population of patients.